The Psychological aspect in building school curriculum - mokrane, fadila (Journal of Social Sciences and Humanities, 2020)
The present paper attempts to show the recognition of the importance of the learner’s psychological aspect when building school curriculum. It highlights the significant position of capabilities and inclinations and previous experiences of the learner, which is a basis for selecting the content of the school curriculum and organizing it, and from it the learner becomes the centre of building the school curriculum. This research started from the achieved results of psychological and educational studies which have put the learner at the centre of the Teaching-Learning process, making of him the main actor. In fact, this new trend represented a revolution against the classical theories that had made of the teacher the main actor and cornerstone of the Teaching-Learning operation. Indeed, a strong need was manifested to highlight the crucial place that should be accorded to the learner’s psychological aspect in the Teaching-Learning process, for the impact it has on educational success or failure. Thus, the classical theories that considered the teacher the main actor in class and the student just a receiver of knowledge were rejected. Indeed, the traditional school curriculum which concentrated on making the learner acquires knowledge and learn by heart the information, and ignored his psychological aspect, realized the failure of the teaching process. Accordingly, it became prerequisite to take into account the learner’s personality in all aspects of its growth and make of the psychological basis a background worth of the name to be defended when building school curriculum. This, in fact, leads us to ask the following questions: what is the importance of the psychological aspect in the Teaching-Learning process? And what is its relationship with the school curriculum?